In Vitro Detection of Simulated Apical Root Perforation with Two Electronic Apex Locators - Nazari Moghaddam, Kiumars; Nazari, Shahrzad; Shakeri, Leila; Honardar, Kiamars; Mirmotalebi, Farshid (Iranian Endodontic Journal, 2010)
INTRODUCTION: The aim of this study was to evaluate the accuracy of two electronic apex locators (Smarpex and NovApex) in detecting apical perforation. MATERIALS AND METHODS: After access cavity preparations, the working length was determined by the first examiner before and after perforation with a stereomicroscope by introducing a K-file size 10 into the canal and size 25 K-file up to the perforation site, respectively. The specimens were embedded in a 17-well plastic box containing alginate. The root canals were irrigated with chlorhexidine 0.2% (CHX) through a 27-gauge needle. Two examiners measured the root canal length twice and the mean value was calculated. The data were analyzed using Kolmogorov-Smirnov and ANOVA tests. RESULTS: The results obtained with each Electronic Apex Locator were compared with the corresponding control length. The statistical analysis showed reliable accuracies in detecting the perforation site for the two experimental electronic apex locators (60% and 80% for NovApex and Smarpex, respectively). CONCLUSION: Although no significant difference was shown between Smarpex and NovApex, these results suggest that electronic apex locators can effectively and reproducibly detect root canal perforations.